Pertumbuhan Pelacur di Komunitas Sumber Utama Pelacur - Ima Sri Rahmani (‎‎‎TAZKIYA Journal of Psychology, 2003)
The development of prostitutes in prostitute-producing communities has led to the emergence of different values and ideologies of thinking in prostitute-producing communities. This has led to the emergence of social problems and also sexually transmitted diseases in the area. Therefore, there needs to be a role for the government to overcome and prevent this from continuing to develop. This research aims to see how psychological influences play a role in the community environment that produces prostitutes.